Burden of lip and oral cavity cancer among young people across South, East, and Southeast Asia: trends from 1990 to 2021 and predictions to 2030 - Chen, Hui; Hu, Meiling; Feng, Meiling; Chen, Xueru; Guo, Xuan; Guo, Jincai (Frontiers in Oncology, 2026)
BackgroundLip and oral cavity cancer (LOC) is a major public health challenge in Asia. Nevertheless, a critical gap remains in understanding the epidemiological burden of LOC among young people (15–44 years) in the region. This study aims to analyze the burden and risk factors of LOC in this age group across the four Global Burden of Disease (GBD) Asian regions from 1990 to 2021 and projects trends to 2030.MethodsData on the incidence, deaths, disability-adjusted life years (DALYs), and risk factors of LOC from 1990 to 2021 were obtained from the GBD 2021 study for East, South, Southeast Asia, and High-income Asia Pacific. This study assessed the LOC burden among young people (15–44 years) through age- and sex-stratified analyses, evaluated temporal trends via joinpoint regression, examined risk factor contributions, and projected trends to 2030 using the Nordpred age-period-cohort model.ResultsFrom 1990 to 2021, the age-standardized incidence rate (ASIR) increased across all subregions, with the largest rise in East Asia. In contrast, age-standardized mortality rate (ASMR) and age-standardized DALYs rate declined everywhere except South Asia. In 2021, South Asia bore the heaviest LOC burden among young people in the four Asian subregions. India reported the highest incident cases, deaths, and DALYs in 2021, and Pakistan had the highest ASR for all three metrics. Taiwan (Province of China) showed the largest increase in ASRs over the period. In 2021, smoking had the highest contribution in East Asia, alcohol use in High-income Asia Pacific, and chewing tobacco in South Asia. Projections to 2030 indicate rising ASIR in East, South, and Southeast Asia but declines in High-income Asia Pacific; decreasing ASMR everywhere except South Asia; and increasing age-standardized DALYs rate in East and South Asia but decreases elsewhere.ConclusionsLOC imposes a substantial and growing burden on young people in South, East, and Southeast Asia, marked by rising ASIR since 1990 and projected increases through 2030. South Asia faces the most urgent challenge with concurrent rises in incidence, mortality, and DALYs—most notably in the 20–24 age group. Region-specific interventions targeting predominant risk factors are critically needed.